DMSP Poynting Flux: Data Processing and Inter‐Spacecraft Comparisons. Issue 8 (8th August 2022) - Kilcommons, Liam M.; Knipp, Delores J.; Hairston, Marc; Coley, W. Robin
Abstract: Poynting flux (PF) calculated from low Earth orbit spacecraft in situ ion drift and magnetic field measurements is an important measure of energy exchange between the magnetosphere and ionosphere. Defense Meteorological Satellite Program (DMSP) spacecraft provide an extensive back‐catalog of ion drift and magnetic perturbation measurements, from which quasi‐steady PF could be calculated. However, since DMSP are operations‐focused spacecraft, data must be carefully preprocessed for research use. We describe an automated approach for calculating earthward PF focusing on pre‐processing and quality control. We produce a PF data set using nine satellite‐years of DMSP F15, F16, and F18 observations. To validate our process we inter‐compare PF from different spacecraft using more than 2, 000 magnetic conjunction events. We find no serious systematic differences. We further describe and apply an equal‐area binning technique to obtain average spatial patterns of PF, magnetic perturbation, electric field and ion drift velocity. We perform our analysis using all components of electric and magnetic field and comment on the adverse consequences of the typical single‐electric‐field‐component DMSP PF approximation on inter‐spacecraft agreement. Including full‐field components significantly increases the relative strength of near‐cusp PF and increases the integrated high‐latitude PF by ∼25%. Plain Language Summary: We describe the processing of observations from approximately 45, 000 Defense Meteorological Satellite Program spacecraft orbits over the course of 3 yr, which can be used to study the climatology of electromagnetic energy transfer (also known as Poynting flux [PF]) between the magnetosphere and ionosphere. Observations from three instruments on three operational spacecraft are used to produce the necessary estimates of electric field and magnetic field perturbations that go into the PF calculation. Our processing pipeline includes data checking, baseline removal, and spatial binning of electric and magnetic field perturbations to produce maps of the individual elements of PF. We bin the results in equal‐area bins for each hemisphere. To verify our work, we provide comparisons of individual measurements made by different spacecraft when they are close to each other in space and time. In general, we find the best agreement when we use all components of available field data. Including full‐field components significantly increases the relative strength of near‐cusp PF and increases the integrated high‐latitude PF by ∼25%. Key Points: We describe the data processing for a new Poynting flux (PF) database and provide code access We provide an inter‐comparison of PF from three Defense Meteorological Satellite Program Spacecraft via a conjunction analysis Use of all electric field components to calculate PF significantly improves the inter‐comparison